Effective Virtual Teams for New Product Development - Ebrahim, Nader Ale; Shamsuddin, Ahmed; Salwa Hanim, Abdul-Rashid; Zahari, Taha (Social Science Electronic Publishing, 2012)
Literature shows the factors that impact on the effectiveness of virtual teams for new product development, are still ambiguous. To address this problem, we developed a research design that included a literature review, a preliminary model and field survey. The literature identified factors which impact on the effectiveness of virtual teams. These factors were then modified by a field survey. We explore the relationship between knowledge worker (people), process and technology in virtual teams. The results of the study suggest that technology and process are tightly correlated and need to be considered early in virtual teams. Software as a service, web solution, report generator and tracking system in effective virtual teams should consider for leading such a new phenomena